Analisis Kinerja Keuangan Pada PT. Bumi Sarana Utama Menggunakan Metode Economic Value Added (EVA) - Mansurya, Mansurya; Akbar Idris, Abdi; Anwar, Anwar (CV RIFAINSTITUT, 2021)
This study aims to analyze the financial performance of PT. Bumi Sarana Utama during 2015 to 2019 using the method Economic Value Added (EVA). Data collection used using documentation techniques. The results showed that the value of the Economic Value Added (EVA) of PT. Bumi Sarana Utama during 2015, 2016, 2018, and 2019 was negative (EVA < 0) which means the company is not able to provide or generate economic added value in its operational activities. Even though they had a positive value in 2017, they could no longer maintain this condition in 2018 and 2019. This was due to a consistent decline in operating profit (NOPAT) and changes in the capital structure whose value fluctuated and tended to decline as a result of the changing urgency of asphalt demand. to the concrete and make the EVA value of PT. Bumi Sarana Utama continues to have a negative trend.